Review of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) III. The trilineata species group, with descriptions of four new species - Wang, Shuxia; Jia, Yanyan (Zootaxa, 2018)
The trilineata species group of the genus Promalactis Meyrick, 1908 is proposed for the first time based on the forewing patterns. A total of 36 species are included, four of which are described as new: P. aggregata sp. nov., P. apicifurcellata sp. nov., P. stenitubilaris sp. nov. and P. albipedalis sp. nov. Photographs of adults and genitalia of the new species are provided. A checklist of the other described species belonging to this group is given with original citations.